2022
DOI: 10.4068/cmj.2022.58.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio in Neuroendocrine Carcinoma

Abstract: Extra-pulmonary neuroendocrine carcinoma is a rare and aggressive cancer. Although several biological and histological markers have been suggested as prognostic factors for this cancer, the prognostic importance of systemic inflammatory markers, including the neutrophil-lymphocyte ratio and platelet-lymphocyte ratio, is unclear. This study aimed to evaluate the association between systemic inflammatory markers and the prognosis of extra-pulmonary neuroendocrine carcinoma. We retrospectively analyzed the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Counts of lymphocytes, neutrophils, platelets, and monocytes are all included in a complete blood count. Over the past decade, there has been substantial evidence that CBC-based biomarkers, such as NLR and PLR, have good prognostic value for a variety of cancers ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Counts of lymphocytes, neutrophils, platelets, and monocytes are all included in a complete blood count. Over the past decade, there has been substantial evidence that CBC-based biomarkers, such as NLR and PLR, have good prognostic value for a variety of cancers ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…NLR is one of the most accepted prognostic indices and has a positive correlation to disease severity, progress, and mortality, reflecting the immune system's sufficiency and its ability to "fight" inflammation. It is thus applicable to a variety of disease conditions, from carcinomas to inflammatory bowel and cardiovascular diseases [48][49][50][51][52][53]. In a recent study of ours on cardiac surgery patients, the NLR values on post-operative days 5 and 7 demonstrated significant discriminatory efficacy for predicting mortality within 90 days [54].…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have shown that PLR is a valuable inflammation biomarker in various diseases (27)(28)(29)(30), and some trials have also assessed the relationship between PLR and ICH outcomes. Still, these trials reported inconsistent results, and the relationship between PLR and ICH mortality has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%